Red-to-blue paper-based colorimetric sensor integrated with smartphone for point-of-use analysis of cerebral AChE upon Cd2+ exposure. Issue 2 (6th January 2021) - Liu, Chang; Luo, Yuxin; Wen, Huijie; Qi, Yanxia; Shi, Guoyue; Deng, Jingjing; Zhou, Tianshu
Abstract : A red-to-blue paper-based colorimetric sensor integrated with a smartphone was developed for point-of-use analysis of cerebral AChE upon Cd 2+ exposure. Abstract : Herein, combined with a pervasive smartphone installed with a color recognition app, dual-responsive CDs@Eu/GMP ICPs were designed as a red-to-blue paper-based colorimetric sensor for the point-of-use analysis of cerebral acetylcholinesterase (AChE) upon Cd 2+ exposure. Blue-emitting CDs with multi-functional groups as guests were encapsulated into the network of Eu/GMP ICPs to obtain CDs@Eu/GMP ICPs with the sensitized red fluorescence of Eu 3+ . With the presence of thiocholine (TCh), derived from acetylthiocholine (ATCh) hydrolyzed by AChE, the coordination environment of the CDs@Eu/GMP ICPs was interrupted, leading to the collapse of the CDs@Eu/GMP ICP network and the corresponding release of guest CDs into the surrounding environment. Consequently, the sensitized red fluorescence of Eu 3+ decreased and the blue fluorescence of the CDs increased. This obvious red-to-blue fluorescent color changes of CDs@Eu/GMP ICPs on test paper could then be integrated with the smartphone for point-of-use analysis of cerebral AChE upon Cd 2+ exposure, which not only offers a new analytical platform for a better understanding of the environmental risk of Alzheimer's Dementia (AD), but also holds great potential in the early diagnosis of AD even at the asymptomatic stage with the decrease in CSF AChE as an early biomarker.